(untitled) (Research, Society and Development, 2022)
Eye-tracking studies explore visual photographic perception from a variety of perspectives, as a renewed approach to traditional assessment. The present article aimed to evaluate the esthetic visual perception of laypeople on the lower third of the face, simulating an Angle Class I, Class II, and Class III profile. Class I (straight profile), Class II (mandibular retrognathism), and Class III (mandibular prognathism) were analyzed through a series of edited profile photographs, in the magnitudes of 2.5 mm 5mm, and 7.5 mm in male and female subjects. The changes occurred only in the lower third of the face and the maxilla remained unchanged. The scanning trace of 60 laypeople raters (30 males and 30 females) were recorded using the eye-tracker hardware and the Ogama software to visualize the ocular movement in areas of interest. Heat maps and dots maps were generated by the software to evaluate the main regions of ocular fixation. Each subject was asked to score the attractiveness of each profile separately using a visual analog scale. One-way ANOVA was performed to identify statistically significant differences (p < 0.05). Regarding the heatmaps, the perception of lip called great attention from the laypeople. Statistical difference was found for a complete-time of fixation between Class I and Class II 5mm (p=0.029) for the female model, Class I and Class III 7.5mm (p=0,028), Class I and Class II 7.5mm (p=0,013) for the male subject, where the images with the alterations called more attention than with the Class I for both models. As for attractiveness scores, Class, I for the female and male models were considered more attractive. The lower and upper lip demonstrated an influence on profile perception for alterations of 7.5mm in class III for males and females. Class I was considered more attractive for both models. More aged evaluators tented to give higher grades for attractiveness.